THE IMPACT OF SAND MINING TOWARD FISHERMEN INCOME IN KOTALAMA VILLAGE KUNTO DARUSSALAM SUBDISTRICT ROKAN HULU REGENCY RIAU PROVINCE - Trisnani '; Lamun Bathara; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted on November 2015 in Kotalama village districts Kunto Darussalam Rokan Hulu Riau Province. The choice of location research done purposively or intentionally, with the consideration that there are areas of the river has become legally sand mining carried out by local people. The survey methode was used by case study in which by direct observation in the field, data collection was done by direct interviews with respondents based on the questionnaire that has been provided. Results of the research by the sand mining reduced the number of fishermen from ± 30 fishermen was reduced to 15 fishermen. The average income of the fishermen from the fishing in the river before and after at Rokan River sand mining activities before sand mining premises that the average ± Rp 2.733.000 and after sand mining decreased fishing revenue is ± Rp 1.446.000 this is due to lack of population polluted fish and the waters of the Rokan River. Sand mining activities have a positive impact and negative impact is felt by the local community to the social and environmental. Positive impact on the social is opening up jobs for the community, insufficient sand for the needs of the Development area as well as individuals and can develop creative power of the community, while the negative impact of his on the environment is the destruction of roads because frequently traveled by trucks of sand and the health impacts of society disrupted by of smoke and dust of the sand transport vehicle, the noise around river sand mining activities, pollution of waters in rivers such stem Rokan, and abrasion around the edge of the river..Keyword :Sand Mining,Income of Fishermen